General Evolution of the Universe Driven by Attraction and Four Levels of Biological Evolution as its Essential Part - George, Mikhailovsky (Journal of Evolutionary Science, 2018)
A strict definition of the hierarchy of material systems is formulated. Based on this definition, the main hierarchical structure of the Universe was divided to 15 levels belonging to 2 branches. Process of the Universe evolution (megaevolution) is considered as hierarchogenesis, i.e., a process of new hierarchy levels formation. The main driver of the hierachogenesis is an attraction that takes different forms for different steps of the megaevolution. Duration and time of each this step on the Universe timeline were estimated using the data of the other investigators. Biological evolution is considered as essential part of the general megaevolution where symbiosis plays role of the hierarchogenetic attraction. Semantic consideration of the hierarchogenesis allowed to build a mathematical model of its dynamics. It appeared that this model describes general megaevolution of the Universe well enough to estimate time of macromolecules appearance, that is still unknown, and to predict when the next hierarchogenetic step will take a place.
Keywords: Biological Evolution; Hierarchogenetic branches; material evolution